ANALISIS PENANAMAN NILAI KARAKTER SOSIAL DALAM EKSTRAKURIKULER PALANG MERAH REMAJA DI SMAN 6 PONTIANAK - Ria Andriani; Achmadi Achmadi; Thomy Sastra Atmaja (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the planning of programs, the implementation ofprograms, and the relevance of extracurricular activities in instilling thecharacter values of social care in SMA Negeri 6 Pontianak. The research methodused is descriptive with a qualitative research approach. Sources of data in thisstudy were PMR members, trainers, and coaches, and the data were interviewsheets for informants, observation sheets, and secondary data from PMRmembers. The results showed that: 1) planning of Palang Merah Remaja (PMR)activity programs at SMA Negeri 6 Pontianak was carried out in 2 odd-evensemesters and as for PMR extracurricular work program, training for batch 5,first aid training, inauguration of batch 5, slayer taking. 2) the implementation ofeach Palang Merah Remaja program at SMA Negeri 6 Pontianak has the mainobjective of improving the quality of the Youth Red Cross, and increasing thecharacter of PMR members' social care for others. 3) from each implementationof the Palang Merah Remaja (PMR) activity, it has an impact on the developmentof social caring characters such as the character of help, tolerance, tolerance,social action, and noble character.Keyword: Character Education, PMR, Social Care